352 THE IMPACT OF ETHNICITY ON ACUTE STROKE ADMISSIONS IN AN IRISH HOSPITAL. (25th October 2022) - Roche, A; Duane, C; Murchan, A; Donaghy, L; Guilfoyle, P; Dolan, E; Sheehan, O
Abstract: Background: Recent studies have demonstrated the variability of aetiology, clinical presentation and overall mortality between different ethnic groups presenting with acute stroke. The non-native Irish population accounts for almost 13% of the total population and is predicted to grow over the next decade. Recording and analysis of acute stroke patients based on their ethnicity and population demographics is an important step in planning for the future of stroke care in Ireland. In this study, we aimed to evaluate key differences between the Irish and non-Irish population presenting with acute stroke to an Irish hospital. Methods: We reviewed our hospital stroke registry over a 12-month period (January-December 2021). Key parameters including country of birth, ethnicity, other patient demographics, clinical presentation, aetiology and subtype of stroke, stroke management and clinical outcomes. Results: Of the 245 acute strokes admitted to our hospital in 2021, non-ethically Irish patients made up 12.2% (n = 30). The average age of non-ethnically Irish stroke presentations was younger than Irish stroke presentations (59 versus 71 years). Haemorrhagic strokes were more common in the non-Irish population (13.3% in non-Irish cohort vs 9.8% in Irish cohort). Median time of symptom onset to presentation to hospital was 3 hours and 58 minutes in the Irish patients and 6 hours and 10 minutes in the non-Irish patients. The overall length of stay in hospital post stroke was similar between the two population groups at an average of 19 days duration. Conclusion: This study identifies disparities in acute stroke presentation between the Irish and non-Irish population presenting to an Irish hospital. This study demonstrated the importance of further research on a national scale to record the variability of strokes in different ethnic groups in order to adequately plan primary and secondary stroke care and provide targeted public health campaigns to remain inclusive to Ireland's growing and increasingly diverse population.